Collagen ultrastructure and TGF-beta 1 expression preserved with aminoguanidine during wound healing in diabetic rats - YAVUZ, DİLEK; HAKLAR, GONCAGÜL (TAYLOR & FRANCIS INC, 2005)
Advanced glycoxidation end products have been implicated in delayed diabetic wound healing. In this study, we evaluated the effects of aminoguanidine, which is an advanced glycation and nitric oxide ( NO) synthase inhibitor, on extracellular matrix protein expression, collagen configuration, and nitrite/nitrate levels in wounds of diabetic rats. Sixteen Wistar male rats were made diabetic by streptozotocin. Of these, eight rats were given AG ( aminoguanidine bicarbonate ( AG) ( group DAG) in their drinking water, and eight rats were followed as diabetic paired controls ( group D). Eight healthy rats were followed as the healthy control group ( group H). At the eighth week, a 2 x 2 cm area full-thickness skin defect was created. The degree of contraction of the open wounds was evaluated for 2 weeks duration. On the 15th postoperative day, wound surface areas were measured, and wound specimens and blood samples were collected. The shrinking percentage of the wounds was small in both groups H and DAG compared with group D ( p < 0.05). Similar to healthy rats, the aminoguanidine-treated diabetic rats had very strong transforming growth factor ( TGF)-beta 1 expression in granulation tissue and intact skin in comparison with diabetic controls. In the diabetic group, the intact skin demonstrated sparsely distributed regular collagen fibers in the granulation zone, and the regular pattern of collagen fibers was lost. In conclusion, aminoguanidine improves wound healing, restores growth factor TGF-beta 1 expression, and preserves collagen ultra structure, whereas it has no prominent effect on NO levels within wound tissue in diabetic rats.
Keywords: advanced glycation end products; aminoguanidine; wound healing; TGF-beta; dermal collagen; nitric oxide; lipid peroxidation; streptozotocin-induced diabetes; ENDOTHELIAL GROWTH-FACTOR; NITRIC-OXIDE SYNTHESIS; LIPID-PEROXIDATION; END-PRODUCTS; NONENZYMATIC GLYCOSYLATION; INHIBITION; GLYCATION; MOUSE; MICE; COMPLICATIONS